-10(X-6)=6(10+2X)

Simple and best practice solution for -10(X-6)=6(10+2X) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(X-6)=6(10+2X) equation:


Simplifying
-10(X + -6) = 6(10 + 2X)

Reorder the terms:
-10(-6 + X) = 6(10 + 2X)
(-6 * -10 + X * -10) = 6(10 + 2X)
(60 + -10X) = 6(10 + 2X)
60 + -10X = (10 * 6 + 2X * 6)
60 + -10X = (60 + 12X)

Add '-60' to each side of the equation.
60 + -60 + -10X = 60 + -60 + 12X

Combine like terms: 60 + -60 = 0
0 + -10X = 60 + -60 + 12X
-10X = 60 + -60 + 12X

Combine like terms: 60 + -60 = 0
-10X = 0 + 12X
-10X = 12X

Solving
-10X = 12X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-12X' to each side of the equation.
-10X + -12X = 12X + -12X

Combine like terms: -10X + -12X = -22X
-22X = 12X + -12X

Combine like terms: 12X + -12X = 0
-22X = 0

Divide each side by '-22'.
X = 0

Simplifying
X = 0

See similar equations:

| -4x+4(3x-13)=-140 | | 4x+8x+6x=24 | | -4(3-3m)=-37+7m | | 2(g-h)=b+y | | 9/7*-9/5 | | x^4-2x^3+14x^2-18x+45=0 | | 8k-k-5k+7-2k= | | -15+x+1=31 | | -4(2u-6)=-4-12u | | (6/5x)-(5/8)=(3/4x) | | -12-8(x-3)=-6(x-1) | | 6x-11x-12=-3(x-2) | | -(1+8X)=6-9X | | -9(10x+11)=351 | | 4-2y-y=2 | | tanx=(3/2)^(1/3) | | d=7+5x-8x | | 2x=1.8 | | 6-5x=9x-10x-6 | | 3x+7=8x-63 | | -12=-7–7/2s | | 14+7K=9K-2 | | -8(10x+3)=376 | | f(x)=4x^2-24x+31 | | 19v=-114 | | 3+4(x+6)=11 | | -9=2/3x–17 | | 8-4x=4-3(2x-6) | | 5(8v-8)=-6 | | 2x+3=-55 | | Y=1/2X-18 | | 65=5(5x-17) |

Equations solver categories